PKN2 enhances the immunosuppressive activity of polymorphonuclear myeloid-derived suppressor cells in esophageal carcinoma by mediating fatty acid oxidation - Xiao Fu; GuoQing Zhang; ZhiChao Hou; TingTing Fu; GuangHui Cui (Molecular Medicine)
Abstract Background Myeloid-derived suppressor cells (MDSCs) in tumor microenvironment reduce the efficacy of immunotherapy. PKN2 plays a role in colon cancer, but its function in esophageal cancer (EC) remains unclear. This study investigated PKN2 expression in MDSCs derived from EC tissues and determined whether PKN2 regulates immunosuppressive activity of MDSCs by mediating fatty acid oxidation (FAO). Materials and methods PKN2 expression was determined in GEO database, EC patients, and 4-NQO-induced EC mice, as well as in different types of immune cells. The effect of PKN2 on the function of polymorphonuclear myeloid-derived suppressor cells (PMN-MDSCs) was investigated by co-culture of PMN-MDSCs and CD4+/CD8+ T cells. The co-culture of patient-derived organoids and autologous immune cells was performed to observe the effect of PKN2 on the immunosuppressive function of PMN-MDSCs. Results PKN2 is highly expressed in EC tumor tissues compared to normal tissues, especially in tumor-infiltrated PMN-MDSCs. Overexpressing PKN2 in PMN-MDSCs contributes to the immunosuppressive activity of PMN-MDSCs in vitro. PKN2-overexpressing PMN-MDSCs inhibited the killing ability of cytotoxic T lymphocytes and promoted EC organoid growth. PKN2 promotes FAO in PMN-MDSCs via CPT1B (a key enzyme of FAO). Mechanistically, PKN2 promotes CPT1B transcription by upregulating STAT3 phosphorylation. Conclusions PKN2 expression was increased in PMN-MDSCs derived from human and mouse EC tissues. PKN2 plays a role in enhancing the immunosuppressive activity of PMN-MDSCs by facilitating STAT3 phosphorylation and CPT1B transcription, which in turn leads to increased CPT1B-mediated FAO in PMN-MDSCs. Targeted inhibition of PKN2 is expected to improve immunotherapeutic efficacy in EC patients.